Case Report: A family history of peanut allergy and hereditary alpha-tryptasemia - Chantran, Yannick; Renaudin, Hélène; Arock, Michel; Guiddir, Tamazoust; Nemni, Ariane (Frontiers in Allergy, 2024)
Context Hereditary alpha-tryptasemia (HαT) is associated with elevated basal serum tryptase (bST) and is associated with a higher risk of severe anaphylactic reactions in patients with clonal mast cell disorders or IgE-mediated Hymenoptera venom-induced anaphylaxis. The consequence of this genetic trait remains to be determined in other allergic diseases and food allergy in particular. Objectives Here, we describe three cases of peanut allergy among siblings from a single family of four: two of them were associated with HαT, and the third one was associated with the tryptase wild-type genotype. Methods TPSAB1/TPSB2 genotypes were determined by digital PCR. After the case description, we provided a review of the literature regarding bST levels and tryptase genotypes in anaphylaxis, with a particular focus on food allergy. Results Compared to the sibling with the conventional tryptase genotype, the two siblings with HαT presented a lower peanut threshold at the initial oral food challenge, higher peanut skin prick test reactivity, higher levels of specific IgE to peanut, Ara h 2, and Ara h 6, and a lower IgG4/IgE ratio after 10 years of oral immunotherapy. Conclusion The tryptase genotype and HαT status might modify the clinical presentation and biological features of food allergy.